The Impact of Assisted Hatching on Monozygotic Twinning is Related to Female Age and Insemination Method: A New Perspective. (29th October 2022) - Liu, Chengjun; Su, Ketong; Liu, Gensheng; Shang, Wei; Wang, Xuefang; Li, Chunjin; Chen, Lu; Zhou, Xu
Abstract: Whether assisted hatching (AH) is associated with a higher incidence of monozygotic twinning (MZT) in women undergoing assisted reproductive technology remains controversial; the aim of the study was to demonstrate the relationship between AH and MZT. A total of 8900 clinical pregnancies were selected among embryo transfer cycles from January 2011 to October 2019. Women receiving day (D) 3 embryos were divided into groups A–C: group A ( n = 1651) and group B ( n = 1045) included women aged ≤37 or ≥38 years, respectively, with zona pellucida (ZP) thinning; group C ( n = 3865) included women aged ≤37 years without AH. Women aged ≤37 years who underwent blastocyst transfer and/or blastocyst ZP breaching were included in group D ( n = 2339). The incidence of MZT was compared among groups A, B and C, and between groups C and D. The incidence of MZT in group B (2.2%) was significantly higher than in group A (1.0%), especially following intracytoplasmic sperm injection (ICSI), while the incidence of MZT in group A (1.0%) was significantly lower than in group C (2.2%). The MZT rate with in vitro fertilization was higher in group D (2.8%) than in group C (2.2%), but the MZT rate following ICSI was not significantly different between the two groups. ZP thinning of D3 embryos may increase the risk of MZT in older women (≥38 years), but decrease it in younger women (≤37 years). ZP breaching may be useful to reduce the incidence of MZT in ICSI-generated blastocysts.